2022
DOI: 10.3389/feduc.2022.783684
|View full text |Cite
|
Sign up to set email alerts
|

Effect of teachers’ asynchronous e-feedback and synchronous oral feedback on English language learners’ writing accuracy

Abstract: This research aims to assess the efficacy of electronic feedback (e-feedback) and traditional oral feedback on undergraduate students’ English writing over 12 weeks of teaching. Three treatment groups were involved: Asynchronous written e-feedback through Microsoft Word Track Changes; teacher–student oral metalinguistic conferencing; no feedback control group. Two grammatical features (i.e., conjunctions and articles), the most problematic forms, were targeted to determine the effect of feedback on these gramm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…The findings revealed that the synchronous CF allows for an interactive writing process, is more effective for self-correction and assists metalinguistic perceptions of writing. In their study of undergraduate students' English writing, Nusrat et al . (2022) compared traditional oral feedback with CMCF.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings revealed that the synchronous CF allows for an interactive writing process, is more effective for self-correction and assists metalinguistic perceptions of writing. In their study of undergraduate students' English writing, Nusrat et al . (2022) compared traditional oral feedback with CMCF.…”
Section: Literature Reviewmentioning
confidence: 99%
“…writing. In their study of undergraduate students' English writing, Nusrat et al (2022) compared traditional oral feedback with CMCF. Results showed that students who got electronic input significantly outperformed those who received oral feedback in terms of reducing conjunction errors.…”
Section: Corrective Feedback In Project Supervisionmentioning
confidence: 99%